The financial sector and economic growth in a panel of countries - Klaus Gründler; Jan Weitzel (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, insbes. Wirtschaftsordnung und Sozialpolitik, 2013)
Does the financial sector contribute to economic growth? While most of the studies carried out before the Financial crisis tend to answer the question with 'yes', recent empirical work provides evidence that the opposite is true. We study these new findings in detail, applying GMM and 3SLS estimations of simultaneous equation models that cover a comprehensive set of growth determinants proposed by theory and recent empirical work. It turns out that finance in general exerts a positive influence but this influence vanishes in the development process and eventually becomes negative. While finance still boosts growth in developing countries, a growing financial sector hinders the increase of incomes in rich economies.
Keywords: O40; G20; 330; Economic Growth; Financial Sector